2019
DOI: 10.1371/journal.pone.0210902
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Treponema pallidum, the syphilis spirochete, with human platelets

Abstract: Extracellular bacteria that spread via the vasculature employ invasive mechanisms that mirror those of metastatic tumor cells, including intravasation into the bloodstream and survival during hematogenous dissemination, arrestation despite blood flow, and extravasation into distant tissue sites. Several invasive bacteria have been shown to exploit normal platelet function during infection. Due to their inherent ability to interact with and influence other cell types, platelets play a critical role in alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 80 publications
1
21
0
Order By: Relevance
“…This may suggest that the increased numbers of nucleated cells in the CSF of patients with neurosyphilis may be due to the continuous damage of the vascular endothelial cells of the blood‐brain barrier, rather than due to the direct chemotaxis of monocytes. Interestingly, Church et al reported that T pallidum directly, preferentially, and reversibly interact with activated platelets, alter their movement and blood‐brain barrier permeability, eventually facilitating their dissemination 38 . The increased CSF levels of CCL24, CXCL7, and CXCL8 require further investigation to elucidate the role of eosinophils and neutrophils in neurosyphilis.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that the increased numbers of nucleated cells in the CSF of patients with neurosyphilis may be due to the continuous damage of the vascular endothelial cells of the blood‐brain barrier, rather than due to the direct chemotaxis of monocytes. Interestingly, Church et al reported that T pallidum directly, preferentially, and reversibly interact with activated platelets, alter their movement and blood‐brain barrier permeability, eventually facilitating their dissemination 38 . The increased CSF levels of CCL24, CXCL7, and CXCL8 require further investigation to elucidate the role of eosinophils and neutrophils in neurosyphilis.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately ⅓ of patients with untreated syphilis present with tertiary syphilis 10-30 years following initial exposure, and while rare, thrombosis of the aorta has been reported in syphilitic aortitis, a sequela of the tertiary disease [9]. Recent research studying Treponema pallidum has revealed that it is an invasive bacteria with the ability to readily cross-endothelial barriers through its ability to interact with, and activate platelets [10]. While further research is needed to expound upon these results and to elucidate the mechanisms behind mural thrombus formation in syphilitic aortitis, it aids in explaining the development of thrombosis in the absence of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Common receptors in pathogen transcytosis-based brain entry are the transferrin receptor, insulin receptor and LRP1/LRP2. Treponema pallidum , the causative agent of syphilis, interacts with platelets, allowing it to cross the BBB as well as the placental and retinal barriers [ 111 ]. Using an approach inspired by Cryptococcus neoformans , a cause of fungal meningitis, Aaron and Gelli used a secreted fungal metalloprotease, Mpr1, as a means of increasing quantum dot penetration through an in vitro BBB model [ 112 ].…”
Section: Biomimetic Approaches To Bbb Drug Deliverymentioning
confidence: 99%